The effects of irrigation retirement on soil carbon dynamics of a continuous maize agroecosystem - Mendoza-Martinez, Violeta, author; Schipanski, Meagan, advisor; Wrighton, Kelly, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2023)
Over half of the world's fresh water is used in crop production and, in some key agricultural regions, use far exceeds local water availability and recharge rates. With the increasing strain on freshwater resources caused by climate change and a growing population, agriculture is under pressure to reduce its water consumption and large areas of currently irrigated farmland across the Western U.S. will likely transition into dryland agriculture over the coming decades. The effects this will have on global soil carbon (C) dynamics, however, remain unclear. In 2016, a study was established in Northern Colorado to understand how stopping irrigation affects soil C turnover in a no-till, continuous maize agroecosystem. Earlier results showed limited responses of the soil microbial community to irrigation retirement, but differences in soil heterotrophic respiration (Rh) rates were detected after two years of accumulated differences in plant residue inputs, thus suggesting a possible co-limitation of water and available C to the microbial community. We continued this experiment through 2022 to further explore the relationship between soil moisture and C inputs in shaping the soil microbial community under the new watering regimes and the consequential effects on soil respiration (Rs) as an indicator of soil organic C (SOC) turnover rates. Two seasons of data collection in 2021 and 2022 showed decreases in available soil water, bacteria, fungi, protozoa and actinomycetes fatty acid methyl ester (FAME) biomarkers, activities of four extracellular enzymes and soil autotrophic respiration in response to both reductions in irrigation and plant inputs, with strong interactive effects between the two factors. However, plots under dryland conditions had higher concentrations of dissolved organic carbon (DOC) and muted differences in soil Rh when compared to their irrigated counterparts; differences in Rh between fallow treatments with (YF) and without residue inputs (LTF), on the other hand, were more pronounced. Soil Rs in fallow plots was consistently, positively correlated with field soil temperature, while correlations with moisture were weak or even negative, thus suggesting soil moisture was not a strong direct driver of Rh. We investigated the direct and indirect influences of variables collected monthly across two seasons on soil Rh to test our hypothesized model using structural equation modeling. In contrast to the cumulative treatment level impacts of plant inputs and irrigation, monthly soil moisture measurements had a stronger, direct effect on Rh than substrate availability as estimated by water-extractable DOC. The final model only explained 24% of the variability in soil Rh. Changes in global C dynamics can be expected with transition of land areas from irrigated to dryland agriculture. However, focusing on soil health, resource conservation practices and the resiliency of the soil microbiome can be the key to minimize the potential negative impacts of this transition.
Keywords: corn; long-term; agroecology; maize; dryland